CONTESTING THE COVID-19 CONSENSUS: CONNECTIVE ACTION OF PSEUDOANONYMOUS ACCOUNTS ON FINNISH TWITTER - Heikkilä, Tuomas; Laaksonen, Salla-Maaria; Väliverronen, Esa (AoIR Selected Papers of Internet Research, 2023)
Recent years have witnessed invigorated debate about the contradictions of identity-concealing public participation and its influence on democratic deliberation and policy-making. Some have documented the exploitation of misrepresented identities for manipulation, including the manufacturing and disrupting of political discourses. Others argue that pseudonymous speech fosters less conformist and more secure public spaces for critical social commentary and political activism. In this study, we extend this dichotomy by approaching pseudoanonymous online action as connective action; as focused and communicative political activism aimed to contest the authorities’ Covid-19 response during the pandemic in Finland.Our empirical analysis uses the historical Twitter data, over 4.2 million tweets, by pseudoanonymous Twitter accounts predominantly tweeting about Covid-19 (n = 229). Using mention and retweet networks combined with profile metrics and qualitative reading of tweets filtered through the network analysis, we explore the networked activity of these accounts, the strategies they have employed to contest authorities, and their connections to political actors and other more organized forms of mobilization around Covid-19.The preliminary analysis highlights the prominence of these accounts in Covid-19 related Twitter discussions, along with their distinct behavioural features. Pseudoanonymous accounts average shorter lifespans and higher deactivation rates. Some accounts have transitioned from named accounts towards identity-concealing action during the observation period. Further, our analysis reveals a symbiotic relationship between the pseudoanonymous accounts and the established Covid-19 movements. We argue that pseudoanonymous participation is an increasingly emblematic form of connective action afforded by social media platforms, particularly fitted to undermine the legitimacy of authorities.